Kinetic analysis of Nico electrodeposition with saccharin using electrochemical impedance spectroscopy - Jae-Ik Choi; Inyeol Park; Suyeon Park; Min Jun Yi; Wonbong Jang; Jong Hyun Seo (Electrochemistry Communications)
The reaction kinetics of nickel‑cobalt alloy electrodeposition is investigated through Electrochemical Impedance Spectroscopy (EIS). Results revealed two primary effects of saccharin additives: reducing competition between hydrogen and metal adsorption, and inhibiting reaction by blocking active sites. At low saccharin concentrations, reduced competition led to rapid hydrogen evolution, resulting in non-uniform and rough microstructures. Conversely, saccharin's strong inhibition effect at higher concentrations yielded fine microstructures with mirror-like appearance. These microstructural changes significantly enhanced the hardness and reduced friction of the electrodeposited film. Furthermore, the suppression of hydrogen reactions stabilized the local pH during the electrodeposition, producing high-quality metallic films with reduced oxide/hydroxide impurities. This study paves the way to understand the complex interplay of electroplating additives in metallic-alloy electrodeposition to optimize microelectronics fabrication.